Impact on weight and physical function of intensive medical weight loss in older adults with stage II and III obesity. Issue 9 (19th July 2016) - D. Ard, Jamy; Cook, Miranda; Rushing, Julia; Frain, Annette; Beavers, Kristen; Miller, Gary; Miller, Michael E.; Nicklas, Barb
Abstract : Objective: A 6‐month pilot trial compared two strategies for weight loss in older adults with body mass indexes (BMIs) ≥35 kg/m 2 to assess weight loss response, safety, and impact on physical function. Methods: Twenty‐eight volunteers were randomized to a balanced deficit diet (BDD) (500 kcal/day below estimated energy needs) or an intensive, low‐calorie, meal replacement diet (ILCD, 960 kcal/day). Behavioral interventions and physical activity prescriptions were similar for both groups. Primary outcomes were changes in body weight and adverse event frequency; secondary outcomes included measures of physical function and body composition. Results: ILCD average weight change was −19.1 ± 2.2 kg or 15.9 ± 4.6% of initial body weight compared with −9.1 ± 2.7 kg or 7.2 ± 1.9% for BDD. ILCD lost more fat mass (−7.7 kg, 95% CI [−11.9 to −3.5]) but had similar loss of lean mass (−1.7 kg, 95% CI [−4.1 to 0.6]) compared with BDD. There were no significant differences in change in physical function or adverse event frequency. Conclusions: Compared with a traditional BDD intervention, older adults who have severe obesity treated with intensive medical weight loss had greater weight loss and decreases in fat mass without a higher frequency of adverse events. In the short term, however, this did not translate into greater improvements in physical function.